Building a Speaker Diarization System: Lessons from VoxSRC 2023 - Karamyan, Davit S.; Kirakosyan, Grigor A. (Mathematical Problems of Computer Science, 2023)
Speaker diarization is the process of partitioning an audio recording into segments corresponding to individual speakers. In this paper, we present a robust speaker diarization system and describe its architecture. We focus on discussing the key components necessary for building a strong diarization system, such as voice activity detection (VAD), speaker embedding, and clustering. Our system emerged as the winner in the Voxceleb Speaker Recognition Challenge (VoxSRC) 2023, a widely recognized competition for evaluating speaker diarization systems.